Accuracy Comparison Between Easy Qibla and Total Station - Kasim , M. I. S.; Shariff , N. N. M.; Hamidi , Z. S. (SOTVI, 2025)
Easy Qibla is a mobile app developed by ESERI, UniSZA which provides, other than direction of qibla, azimuth and altitude of the Sun and the Moon on actual time. This data is regularly used by falak or astronomy researchers, therefore the accuracy is critical. This study aims to compare azimuthal data accuracy provided by Easy Qibla and total station by measuring actual azimuth of the Sun and the Moon. A total station is erected on station 1 with station 2 set as the reference object (RO). The azimuth of station 2 from station 1 is pre-determined by GPS device. Sixty-nine readings were taken by observing both the Sun and the Moon. In each observation, screenshots of Easy Qibla were taken, thus capturing the actual time azimuth. The corresponding azimuth of the Sun or the Moon shown on the total station display was recorded. Both readings are tabulated and subtracted to obtain the errors. Results after sixty-nine readings show that the lowest error is 0.0002°, while highest error is 0.26°, with an average of 0.06°. Data collected on another day may give different results due to the differences in the declination of the Sun. The errors are inclusive of, but limited to, human error and total station error. In conclusion, the result shows that the errors are insignificant in considerably low accuracy field of studies like determining qibla or new moon observation.